Business Model and Strategy Development of PT Rev Kreasindo Utama - Novrizal, Aldila; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2015)
Abstract.In the early and mid of 2000s, casual fashion became a trend among youth in Indonesia, especially teenager and young adult, due to the development in music or any other creative activities engaging youth to express their ideas and interests. In the notion of grabbing the business opportunities in this industry, Rev Clothing was founded in 2007. As the company keeps developing, it challenges the fierce competition within the clothing industries involving both local and international brand companies. This thesis aims to analyze the business development of Rev Kreasindo Utama and to draw the business strategy and model that are applicable for the company in order for the company to survive and compete within the industry. For the environmental scanning stage, this process is to analyze both external and internal factors that effect to company. Then, formulating the strategy is also done to decide what strategy that needs to be undertaken by Rev Kreasindo Utama to overcome the obstacles challenged. All of the strategies and business models development must be formulated in its implementation plan so that Rev Kreasindo Utama can easily get solutions to settle the problems faced in running the business.Keywords: Fashion, Casual Fashion, Business Model, and Business StrategyÂ